Private Financing of Public Infrastructure through PPPs in Latin America and the Caribbean - Garcia-Kilroy, Catalina; Rudolph, Heinz P. (World Bank, Washington, DC, 2017)
Financing public infrastructure is an important challenge in the growth agenda of the Latin America and the Caribbean (LAC) region. Subject to fiscal constraints, many countries in the LAC region have been looking at private sector financing as an alternative for financing public investment. With different degrees of success, countries in the region have been using Public-Private Partnerships (PPPs) since the late 1980s. Although the needs of investments in public infrastructure vary by country and by sector, it is clear that public resources might not be enough. While public infrastructure will continue to be largely financed by the public sector in the LAC region, significant room still exist for private sector financing of public infrastructure. In Advanced Economies (AEs), such as Australia, and the United Kingdom, PPP projects account for 10 to 15 percent of overall infrastructure investments. This report analyzes the challenges and policy options to increase private sector financing in public infrastructure in the LAC region through PPPs. Given the diversity of LAC countries, the report takes a conceptual approach and analyzes the different alternatives of private sector financing of public investments that different groups of countries can utilize. This approach also takes stock of the different status and degree of institutional and financial development in LAC countries in light of ongoing promising legal reforms and financial innovations for infrastructure finance in the LAC region, as well as in AEs and other regions.